Addiction to the nicotine gum in never smokers - Etter Jean-François (BMC, 2007)
Abstract Background Addiction to nicotine gum has never been described in never smokers or in never users of tobacco. Methods Internet questionnaire in 2004-2006 in a self-selected sample of 434 daily users of nicotine gum. To assess dependence on nicotine gum, we used modified versions of the Nicotine Dependence Syndrome Scale (NDSS), the Fagerström Test for Nicotine Dependence and the Cigarette Dependence Scale. Results Five never smokers used the nicotine gum daily. They had been using the nicotine gum for longer than the 429 ever smokers (median = 6 years vs 0.8 years, p = 0.004), and they had higher NDSS-gum Tolerance scores (median = 0.73 vs = -1.0, p = 0.03), a difference of 1.5 standard deviation units. Two never smokers had never used smokeless tobacco, both answered "extremely true" to: "I use nicotine gums because I am addicted to them", both "fully agreed" with: "after a few hours without chewing a nicotine gum, I feel an irresistible urge to chew one" and: "I am a prisoner of nicotine gum". Conclusion This is to our knowledge the first report of addiction to nicotine gum in never users of tobacco. However, this phenomenon is rare, and although the long-term effect of nicotine gum is unknown, this product is significantly less harmful than tobacco.